BRAND PERSONALITY TOWARD ATTITUDE AND BEHAVIORAL INTENTIONS VIA BRAND PERSONALITY APPEAL ON GRABBIKE - DESI LESTARINI; AULIA DANIBRATA (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The first purpose of this study is to investigate whether each of brand personality dimension variables has a direct influence to brand personality appeal or not. The second purpose is to demonstrate the utility of brand personality appeal as a mediator as if each brand personality dimension variables has an indirect significant impact towards attitude and behavioral intentions through brand personality appeal in the context of online ride hailing service brand. Data used obtained from direct distribution questionnaires to 140 respondents. Statistical analysis was conducted using SMARTPLS 2.0. Research findings can be summarized as follows. First, Responsibility, Activity, and Aggressiveness Brand Personality has a direct influence and statistically significant in order to predict Brand Personality Appeal. Second, Responsibility, Activity, and Aggressiveness Brand Personality actually has a similar indirect influence and statistically significant in order to predict Attitude and Behavioral Intentions via Brand Personality Appeal.